2022
DOI: 10.1371/journal.pntd.0010145
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of West Nile virus distribution in the Volgograd region of Russia, a territory with long-existing foci

Abstract: Southern Russia remains affected by West Nile virus (WNV). In the current study, we identified the spatial determinants of WNV distribution in an area with endemic virus transmission, with special reference to the urban settings, by mapping probable points of human infection acquisition and points of virus detection in mosquitoes, ticks, birds, and mammals during 1999–2016. The suitability of thermal conditions for extrinsic virus replication was assessed based on the approach of degree-day summation and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 108 publications
0
8
0
Order By: Relevance
“…Besides, decision-tree-based models such as random forest and gradient-boosted tree are popularly used in ecological niche modeling. These models have been widely applied to estimate the potential risk areas of diseases such as malaria ( Bhatt et al, 2017 ), dengue ( Liu et al, 2016 ), West Nile virus ( Shartova et al, 2022 ), scrub typhus ( Acharya et al, 2019 ), brucellosis ( Jia and Joyner, 2015 ), and Chagas disease ( Mischler et al, 2012 ) as well as to estimate the spatial distribution of the vectors of Lyme disease ( Burrows et al, 2022 ), chikungunya ( Richman et al, 2018 ), leishmaniasis ( Cunze et al, 2019 ), and malaria ( Akpan et al, 2018 ). Previous studies have demonstrated the use of boosted regression tree (BRT) to map the geographical distribution of natural reservoirs and vectors of P. knowlesi and estimated the risk of P. knowlesi infection throughout Southeast Asia ( Moyes et al, 2016 ; Shearer et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, decision-tree-based models such as random forest and gradient-boosted tree are popularly used in ecological niche modeling. These models have been widely applied to estimate the potential risk areas of diseases such as malaria ( Bhatt et al, 2017 ), dengue ( Liu et al, 2016 ), West Nile virus ( Shartova et al, 2022 ), scrub typhus ( Acharya et al, 2019 ), brucellosis ( Jia and Joyner, 2015 ), and Chagas disease ( Mischler et al, 2012 ) as well as to estimate the spatial distribution of the vectors of Lyme disease ( Burrows et al, 2022 ), chikungunya ( Richman et al, 2018 ), leishmaniasis ( Cunze et al, 2019 ), and malaria ( Akpan et al, 2018 ). Previous studies have demonstrated the use of boosted regression tree (BRT) to map the geographical distribution of natural reservoirs and vectors of P. knowlesi and estimated the risk of P. knowlesi infection throughout Southeast Asia ( Moyes et al, 2016 ; Shearer et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Wetlands are the most important ecosystems for enzootic transmission of the virus due to the presence of both resident and migratory bird as well as of competent mosquito vectors, particularly Cx. pipiens [60]. Overall, water bodies are considered to favor the activity of mosquitoes and their capacity to complete different life cycle stages [61].…”
Section: Discussionmentioning
confidence: 99%
“…WNV is primarily transmitted by mosquitoes usually of the Culex spp. Although WNV has also been recovered from ticks in Russia, ticks have an unclear role in maintaining or disseminating the virus and their role may be relevant in preserving the virus during the winter [4]. Birds (in particular, Ardeid birds such as herons and egrets) are the primary hosts, and the virus is maintained in a bird-mosquito-bird cycle.…”
Section: Mosquito-borne Transmissionmentioning
confidence: 99%